ESENSI BANTEN BEBAJANGAN PADA UPACARA MEBAJANG COLONG DI DESA KELIKI KECAMATAN TEGALLALANG KABUPATEN GIANYAR (PERSPEKTIF PENDIDIKAN AGAMA HINDU) - I Wayan Janur Divayan; Marsono; I Gusti Ngurah Triyana (UHN IGB Sugriwa Denpasar, 2020)
The values of education in ceremonies are still largely unknown. The form of ceremony that is still not understood about its educational values is the banten bebajangan at the mebajang colong ceremony in Keliki Village. Issues to be discussed include: (1) What is the shape of the Banten Bebajangan at the Mebajang Colong Ceremony in Keliki Village. (2) What meaning is contained in Banten Bebajangan at the Mebajang Colong Ceremony in Keliki Village. (3) What is the value of Hindu Religious Education contained in Banten Bebajangan at the Mebajang Colong Ceremony in Keliki Village. This study aims to determine: (1) the form of Banten Bebajangan at the Mebajang Colong Ceremony in Keliki Village. (2) The meaning of Banten Bebajangan at the Mebajang Colong Ceremony in Keliki Village. (3) The value of Hindu religious education contained in Banten Bebajangan at the Mebajang Colong Ceremony in Keliki Village. The theories used to analyze the problem are: religious theory, symbolic interactionism theory and value theory. Data collection methods are observation, interviews, documentation and literature. The collected data were analyzed by reducing, presenting and drawing conclusions. Based on data analysis, the research results obtained are: (1) The form of the bebajangan offering consists of several types of rivals, namely; tetandingan boki, sorohan alit, tumpeng danan, squeeze, ajuman, pemeneng pebuwu, penjor or gonjer, laban and raka- raka laklak tape. (2) Banten bebajangan has several meanings, namely religious meaning, symbolic meaning, purification meaning, respect meaning and harmony meaning. (3) The values of Hindu religious education contained in banten bebajangan are character values, aesthetic values, ethical values, social values and economic values.